Mitigating cascading failures of spatially embedded cyber–physical power systems by adding additional information links. (September 2022) - Dong, Zhengcheng; Tian, Meng; Li, Xin; Lai, Jingang; Tang, Ruoli
Abstract: To improve the invulnerability of cyber–physical power systems (CPPSs) against cascading failures, this paper develops a spatial CPPS model considering the hierarchical information network and proposes an information link addition strategy with cost constraints. This is a more convenient and low-cost method than adding transmission lines to improve the performance of CPPS without changing the original connections. The hierarchical information network consists of an access layer (AL), a backbone layer (BL) and a core layer (CL), and thus the components are divided into different layers. Depending on the layers to which the added link endpoints belong, three link addition modes, AL–AL, AL–BL and AL–CL, as well as a random mode Rand, are proposed and investigated under two cost constraint scenarios. Statistical results on several IEEE test systems show that the invulnerability of CPPS can be improved by adding additional information links. More specifically, AL–BL performs better when either the number or length of links is limited, especially in the case of severe attacks, while Rand is also a better choice for large length constraints under light attacks. In addition, AL–CL is the worst mode in most cases. These findings can help defenders to protect power systems before attacks. Highlights: A spatial cyber–physical power system model with overlapped components is built. According to different layers, four information link addition modes are proposed. Different link addition modes are compared under different constraints and attacks.